2011
DOI: 10.1002/chem.201002876
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Potential Energy Surface of Selected Carbohydrates’ CH/π Dispersion Interactions Calculated by High‐Level Quantum Mechanical Methods

Abstract: In this study we present the first systematic computational three-dimensional scan of carbohydrate hydrophobic patches for the ability to interact through CH/π dispersion interactions. The carbohydrates β-d-glucopyranose, β-d-mannopyranose and α-l-fucopyranose were studied in a complex with a benzene molecule, which served as a model of the CH/π interaction in carbohydrate/protein complexes. The 3D relaxed scans were performed at the SCC-DFTB-D level with 3 757 grid points for both carbohydrate hydrophobic sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 41 publications
4
50
1
Order By: Relevance
“…Although only π-interactions between the entire sugar face of pyranose and the aromatic amino acid were considered in previous work (61,62,67,76), a range of sugar–π contacts were identified for deoxyribose in the present study, which can involve a single proton, two protons (a bridge), three protons (a face), a lone pair, or both a lone pair and a proton (lone pair–proton; Figures 7B, 8 and 10). As a result, we introduce a classification system for DNA–protein sugar–π interactions based on the sugar edge participating in the contact, which can yield C–H···π and/or lone–pair···π interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only π-interactions between the entire sugar face of pyranose and the aromatic amino acid were considered in previous work (61,62,67,76), a range of sugar–π contacts were identified for deoxyribose in the present study, which can involve a single proton, two protons (a bridge), three protons (a face), a lone pair, or both a lone pair and a proton (lone pair–proton; Figures 7B, 8 and 10). As a result, we introduce a classification system for DNA–protein sugar–π interactions based on the sugar edge participating in the contact, which can yield C–H···π and/or lone–pair···π interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although the strongest interactions occur when a pyranose C–H is directed at the center of the aromatic face (76), the amino acid displays a wide range of locations with respect to the sugar in DNA sugar–π contacts. This implies that the sugar composition plays a large role in determining the preferred geometry of the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of these effects might explain the smaller binding energies calculated here compared to the 2.5 – 5.4 kcal/mol estimated from ab initio calculations. 32 Such C-H/π interactions would be present in the experimental systems, but it was not possible to use the NMR results to calculate the binding energies. The binding energies reported here are due primarily to hydration effects resulting from the liberation of structured water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been suggested that these types of associations are strengthened by interactions between the C-H bonds and the π-clouds of aromatic rings such those of caffeine. 3235 Quantum-mechanical studies have been used to estimate the magnitude of this increase in interaction energy that might result from such interactions. While any such effects would of course be present in the NMR experiments reported here, they would appear in the MM simulations only to the extent that they are captured by the force field parameterization, primarily through the choice of atomic partial charges and van der Waals radii.…”
Section: Introductionmentioning
confidence: 99%
“…There is an enhancement in the carbohydrate-aromatic stacking with an increase in sugar hydrophobicity through methylation, as observed by Morales and co-workers. 10 The interaction of carbohydrates with model compounds, such as benzene, [11][12][13] toluene, 14 naphthalene, 15 p-hydroxytoluene, 16 and 3-methylindole, 17 has been studied by both theoretical and experimental approaches, and it was determined that the CH-π interaction occurs and is more relevant when three CH bonds of the carbohydrate are oriented toward the aromatic system.…”
Section: Introductionmentioning
confidence: 99%